Intracerebral Hemorrhage. A Case Presentation - Idaylí Pérez Rodríguez; Dianarelys Villafuerte Delgado; Rubén Bembibre Taboada; Inti Santana Carballosa (Medisur)
A 70 year-old female patient suffering from a cerebrovascular disease intracerebral hemorrhage type and presented as Le Roux 2 cerebromeningeal hemorrhage subtype with factors for a bad prognosis of neurologic causes and, for diverse complications which evolved in the clinical intensive care service at the University hospital ¨Dr. Gustavo Aldereguia Lima¨ in Cienfuegos city. According to the management stated in the clinical practice guideline of the protocol intervention of this health institution an achievement was obtained when the patient passed from a Rankin 5 state at the admission of the hospital to a Rankin 3 state at the time of discharging from the institution. The survival rate at the time of the last evolution was a Rankin 2.